Factors Affecting Bank-specific and Macroeconomic profitability Determinants of Islamic and Conventional Banks in Pakistan - Mazhar Farid, Chiahti; Wajiha, Shokat; Abdul Khaliq, Alvi; Ambreen, Afzal; Madiha, Afzal; Sobia, Irum; Sofia, Safdar; Parveen, Kaur (Universal Publishers - Boca Raton, Florida, USA, 2021)
This empirical research aims to look at the factors that mark the financial performance of Islamic and traditional banking sector in Pakistan. Theresults of the data signify that gross domestic product and inflation is connectedtothefinancialperformanceofIslamicbanks in all aspectsof profitability ratios and grossdomesticproducthasinsignificantrelation with the return on equity and assets ofconventionalbanks.Inflation has a weighty effect on return of assets of conventional banks.Further results indicate a negative impact of bank size on return of assets Islamic and positive impact on conventional banks. Anegativeimpact of banksizeonreturnonequityofIslamicandpositiveimpactonconventional banks. There is no performance impact of bank size on price earnings ratio. Results alsoindicatethatanegativeperformanceimpactofageofbankonreturn on assets of Islamic and traditional banks.